Studies of plant Parasitic nematodes in sugarcane plants in Meerut district (Uttar Pradesh) (International Journal of Food and Nutritional Sciences, 2022)
phytonematodes (PPN) are microscopic round worms that feed on roots and soil, endoparasitic nematodes enter into the roots feed and reproduce in the roots. Ectoparasitic phytonematodes live in the soil and feed outside the roots. Ectoparasitic nematodes (heterodera spp.) and endoparasitic nematodes (Meloidogyne spp) are serious pest on the sugarcane crops.